Open Source Software No Longer Optional. - Anthes, Gary (Communications of the ACM, 2016)
The article discusses the trend toward open source software development and sharing practices. Topics include the history of the open source software (OSS) movement in relation to programmer Richard Stallman, the role of firms Google Inc. and Microsoft Corp. in adopting open source approaches, and the opinions of computer scientist William Scherlis on open source software.